Pemanfaatan Teknologi Informasi Untuk Meningkatkan Pemasaran Wisata Halal Pantai Lombang Sumenep - Nur Ijabah; Zinka Aldamayatri; Muhammad Arsutil Adlah; Viki Amalia; Atika Kharisma Putri; Nabila Padmasari; Farid Ardyansyah (Institut Nalanda, 2024)
Lombang Village, Batang Batang District, Sumenep Regency is a marine tourism area of Lombang Beach. Although it has become part of a tourism development managed by the government, this tourism still requires the role of the community and surrounding communities in helping the tourism development program by increasing the promotion of lombang beach business with the method of utilizing information technology. Lombang Beach is a tourist attraction that is most visited by the community so that by holding promotions by utilizing information technology it becomes a potential as tourist attraction to be better known and able to move potential tourists to visit it